Cellulose modified epoxy resin adhesive as well as preparation method and application thereof
By oxidizing microcrystalline cellulose to produce dialdehyde cellulose, the thixotropic and thermal expansion problems of epoxy resin adhesives are solved, resulting in low-cost, high-performance epoxy resin adhesives suitable for fields such as electronic packaging, aerospace, automotive manufacturing, and construction engineering.
Patent Information
- Application Number
- CN202511601965.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-04
- Publication Date
- 2026-01-23
AI Technical Summary
Existing epoxy resin adhesives have shortcomings in terms of thixotropy, thermal expansion and cost. They are prone to cracking, especially when bonding with dissimilar materials. Furthermore, traditional thixotropic agents and fillers are expensive and it is difficult to balance compatibility and performance.
By oxidizing microcrystalline cellulose to generate dialdehyde cellulose, a stable three-dimensional network structure is constructed using its reactive aldehyde groups and hydrogen bond network with epoxy resin, improving thixotropy and reducing thermal expansion. At the same time, low-cost, renewable cellulose materials are used to replace expensive additives.
This achieves the effects of high thixotropic index, low coefficient of thermal expansion, and reduced cost of epoxy resin adhesives, significantly improving construction performance and long-term material reliability while reducing raw material costs.
Smart Images

Figure CN121379467A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of epoxy adhesives, in particular to a cellulose modified epoxy adhesive, a preparation method and application thereof. BACKGROUND
[0002] Epoxy adhesives are widely used in electronic packaging, aerospace, automobile manufacturing and construction engineering due to their excellent bonding strength, chemical stability, heat resistance and electrical insulation. However, there are still some technical bottlenecks in the practical application of traditional epoxy adhesives, which restrict their application in high-end and specific scenarios: (1) Insufficient thixotropy: Thixotropy refers to the property of a material that its viscosity decreases under shear force and recovers after standing. For application scenarios such as vertical surface construction, ceiling gluing or precision dispensing, good thixotropy can effectively prevent glue flow and dripping, ensuring the uniformity of the glue layer and the forming quality. Traditional epoxy adhesives often add inorganic thixotropic agents such as fumed silica to improve thixotropy. However, such thixotropic agents are expensive, significantly increasing material costs; and at high addition levels, they can cause the overall viscosity of the system to be too high, the leveling property to be poor, and the mechanical properties and light transmittance of the final glue layer to be affected.
[0003] (2) High coefficient of thermal expansion (CTE): Epoxy resins still have a high coefficient of thermal expansion after curing. When used to bond dissimilar materials with large differences in thermal expansion coefficients (such as metal and ceramic, electronic components and PCB), large internal stresses will be generated during temperature cycling. This internal stress can cause the glue layer to crack, the interface to peel off, and even cause the bonded parts to warp or be damaged, seriously affecting the long-term reliability and service life of the device (such as LED, chip).
[0004] (3) Cost and sustainability pressure: The above-mentioned high-performance thixotropic agents (such as fumed silica) and functional fillers for reducing CTE (such as ceramic microspheres) are expensive. At the same time, the entire chemical industry is facing pressure to reduce dependence on petroleum-based products and develop in a green and sustainable direction. Developing biomass-based additives that are widely available, renewable, biodegradable and low-cost to replace or partially replace traditional petroleum-based or mineral-based additives has become an important research direction in this field.
[0005] Cellulose is the most abundant natural polymer in nature, with advantages such as wide availability, renewability, biodegradability, low cost, high strength and high modulus. In recent years, there has been increasing research on using nanocellulose (CNC, CNF) or modified cellulose as a polymer reinforcing phase. However, untreated cellulose contains a large number of hydroxyl groups, has strong hydrophilicity, poor compatibility with hydrophobic epoxy resin matrix, easily agglomerates, and is difficult to disperse uniformly, which can instead lead to deterioration of material properties.
[0006] Therefore, how to effectively modify cellulose through physicochemical means to overcome its compatibility with epoxy resin, so that it can not only serve as a reinforcing phase, but also simultaneously play multiple roles as a highly efficient thixotropic agent and a low-expansion filler, thus solving the three major defects of traditional epoxy adhesives in terms of thixotropy, thermal expansion, and cost, has become a highly valuable but not yet fully overcome technical challenge. Summary of the Invention
[0007] The purpose of this invention is to overcome the above-mentioned technical deficiencies and provide a cellulose-modified epoxy resin adhesive, its preparation method and application, thereby solving the technical problem in the prior art where the poor compatibility between epoxy resin and cellulose leads to an inability to simultaneously achieve thixotropy, thermal expansion and cost in epoxy resin adhesives.
[0008] To achieve the above-mentioned technical objectives, the technical solution provided by this invention is as follows: In a first aspect, the present invention provides a method for preparing a cellulose-modified epoxy resin adhesive, comprising the following steps: S1, oxidizing microcrystalline cellulose with an oxidant to obtain dialdehyde cellulose A; S2, impregnating and drying dialdehyde cellulose A with a first epoxy resin and a coupling agent to obtain dialdehyde cellulose B; S3, mixing dialdehyde cellulose B, a second epoxy resin, a curing agent and an accelerator to obtain a cellulose-modified epoxy resin adhesive.
[0009] Secondly, the present invention provides a cellulose-modified epoxy resin adhesive prepared by the above preparation method.
[0010] Thirdly, the present invention provides a cellulose-modified epoxy resin coating, which is formed by curing the above-mentioned adhesive.
[0011] Compared with the prior art, the beneficial effects of the present invention include: This invention treats microcrystalline cellulose with an oxidizing agent to obtain an amphiphilic dialdehyde cellulose. This dialdehyde cellulose possesses epoxy resin-friendly aldehyde groups that can react with epoxy groups, ensuring good compatibility with the epoxy resin matrix, uniform dispersion, and preventing agglomeration. It also contains functional groups capable of forming a strong hydrogen-bonded network, constructing a stable three-dimensional network structure in the resin system. This results in extremely high viscosity in a static state, preventing sagging. Under shear force, the network structure rapidly breaks down, reducing viscosity and facilitating application. This imparts an excellent high thixotropic index to the adhesive. Furthermore, the uniformly dispersed rigid cellulose microfiber skeleton effectively restricts the thermal motion of epoxy resin molecular chains, significantly reducing the coefficient of thermal expansion of the cured adhesive layer. The invention also ensures the activity of the aldehyde groups by directly impregnating the oxidized wet dialdehyde cellulose with a first epoxy resin and a coupling agent, effectively preventing agglomeration. This invention significantly improves the thixotropic index and volume expansion rate of the resin through the reinforcing effect of dialdehyde cellulose, and the process is simple and low-cost. Attached Figure Description
[0012] Figure 1 The images are polarized light microscope images of the prepared resin adhesives; where (a) is the EP of Comparative Example 2, (b) is the MEP of Comparative Example 3, (c) is the 0.3DEP of Comparative Example 1, (d) is the 0.6DEP of Example 1, (e) is the 0.9DEP of Example 2, and (f) is the 1.2DEP of Comparative Example 4. Figure 2 Infrared spectra of the prepared dialdehyde cellulose and the microcrystalline cellulose used; Figure 3 The graph shows the viscosity test results of the prepared resin adhesive. Figure 4 The thixotropic index results of the prepared resin adhesive are shown in the figure. Figure 5 The graph shows the test results of the expansion rate of the prepared modified epoxy resin E51 adhesive at different temperatures. Figure 6 The figure shows the test results of the swelling rate of the prepared modified polyethylene glycol diglycidyl ether adhesive. Detailed Implementation
[0013] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0014] To address the shortcomings of existing technologies where poor compatibility between epoxy resin and cellulose leads to a trade-off between thixotropy, thermal expansion, and cost in epoxy resin adhesives, this invention provides a cellulose-modified epoxy resin adhesive, its preparation method, and its application. This adhesive exhibits excellent overall performance and low cost.
[0015] In a first aspect, the present invention provides a method for preparing a cellulose-modified epoxy resin adhesive, comprising the following steps: S1, microcrystalline cellulose is oxidized with an oxidizing agent to obtain dialdehyde cellulose A; S2, dialdehyde cellulose A is impregnated and dried with a first epoxy resin and a coupling agent to obtain dialdehyde cellulose B; S3, mix dialdehyde cellulose B, second epoxy resin, curing agent and accelerator to obtain cellulose modified epoxy resin adhesive.
[0016] Preferably, in step S1, the oxidant includes sodium periodate.
[0017] Preferably, in step S1, the mass ratio of oxidant to microcrystalline cellulose is (0.3-1.2):1, and more preferably (0.6-0.9):1.
[0018] In this invention, when too little oxidant is added, the degree of oxidation of microcrystalline cellulose is low, and it cannot effectively modify epoxy resin; when too much oxidant is added, the cost is high, and the effect on improving product performance is limited, or even inhibits certain properties, such as causing local over-crosslinking or self-crosslinking agglomeration.
[0019] Preferably, in step S1, the oxidation treatment involves adding an oxidant to the microcrystalline cellulose suspension and then reacting it at 30°C to 60°C for 4 to 10 hours.
[0020] More preferably, the concentration of the microcrystalline cellulose suspension is 0.03–0.1 g / mL.
[0021] Preferably, in step S2, the dry weight of dialdehyde cellulose A accounts for 5% to 15% of the mass of the cellulose-modified epoxy resin adhesive.
[0022] It should be noted that, in order to ensure the activity of the aldehyde groups in dialdehyde cellulose and avoid aggregation, it is necessary to first impregnate the dialdehyde cellulose with a portion of epoxy resin. During the impregnation process, it is not necessary to pre-dehydrate dialdehyde cellulose A; instead, it is directly mixed with the first epoxy resin and coupling agent before drying. This effectively removes water while ensuring the activity of the aldehyde groups in the dialdehyde cellulose. To control the actual amount of dialdehyde cellulose A added, it is limited to its dry weight. The dry weight of dialdehyde cellulose A taken during the operation can be obtained by taking samples, freeze-drying them to obtain the moisture content, and then converting the result.
[0023] Preferably, in step S2, the ratio between the first epoxy resin and the coupling agent is (2-4) g: (0.1-0.2) mL.
[0024] Preferably, in step S2, the coupling agent includes silane coupling agent KH550.
[0025] Preferably, both the first epoxy resin and the second epoxy resin comprise epoxy resin E51 or polyethylene glycol diglycidyl ether.
[0026] Preferably, the mass ratio of the first epoxy resin to the second epoxy resin is (1.5 to 2.5):1.
[0027] Preferably, in step S2, the drying method is freeze drying.
[0028] Preferably, in step S3, the curing agent is methylhexahydrophthalic anhydride or methyltetrahydrophthalic anhydride; the amount of curing agent is 80% to 120% of the total mass of the first epoxy resin and the second epoxy resin.
[0029] Preferably, in step S3, the accelerator includes one or more of triethanolamine, 2-methylimidazole, and 2-ethyl-4-methylimidazole (2-4-EMI); the amount of accelerator used is 0.2% to 0.8% of the total mass of the first epoxy resin and the second epoxy resin.
[0030] Preferably, in step S3, after mixing, the mixture undergoes a defoaming process until no visible bubbles remain.
[0031] Secondly, the present invention provides a cellulose-modified epoxy resin adhesive prepared by the above preparation method.
[0032] Thirdly, the present invention provides a cellulose-modified epoxy resin coating, which is formed by curing the above-mentioned adhesive.
[0033] Preferably, the curing temperature is 80℃~130℃; the curing time is 1 h~4 h.
[0034] The main mechanism of action and advantages of this invention are as follows: (1) This invention prepares an amphiphilic cellulose derivative, namely dialdehyde cellulose, by treating microcrystalline cellulose with oxidants such as sodium periodate. The molecular chain of this derivative simultaneously has epoxy resin-loving segments (i.e., segments containing aldehyde groups), functional groups that can form a strong hydrogen bond network, and a highly rigid cellulose skeleton. The generated aldehyde groups can react with epoxy groups, ensuring good compatibility with the epoxy resin matrix, enabling uniform dispersion and avoiding agglomeration. The functional groups that can form a strong hydrogen bond network (i.e., unreacted segments) construct a stable three-dimensional network structure in the resin system, giving it extremely high viscosity in a static state (anti-sagging). Under shear force, the network structure is rapidly destroyed, reducing viscosity (easy to apply), thus giving the adhesive an excellent high thixotropic index. The uniformly dispersed rigid cellulose microfiber skeleton can effectively restrict the thermal motion of the epoxy resin molecular chains, significantly reducing the coefficient of thermal expansion (CTE) of the cured adhesive layer.
[0035] (2) In this invention, the wet dialdehyde cellulose A obtained by oxidation treatment is directly impregnated with a first epoxy resin and a coupling agent, which ensures the activity of the aldehyde group and effectively avoids agglomeration.
[0036] (3) The present invention uses low-cost, renewable cellulose raw materials: it successfully replaces expensive fumed silica and special fillers with low-cost biomass materials, which significantly reduces the cost of raw materials.
[0037] The present invention will be further described in detail below through specific embodiments.
[0038] Example 1 A method for preparing a cellulose-modified epoxy resin adhesive includes the following steps: S1, Synthesis of dialdehyde cellulose: 20 g of microcrystalline cellulose (MCC) was added to a 500 mL beaker, followed by 300 mL of deionized water. The beaker was sealed, and the mixture was magnetically stirred at 300 r / min for 30 min at 45 °C. Then, 12 g of sodium periodate (NaIO4) was added, resulting in a sodium periodate to microcrystalline cellulose mass ratio of 0.6 g / g. The reaction was continued at 45 °C with magnetic stirring for 9 h. After the reaction, the mixture was filtered through a Büchner funnel and washed five to six times with plenty of deionized water to obtain dialdehyde cellulose A (denoted as 0.6DAC). The product was weighed, and a small amount was weighed and freeze-dried to calculate the yield and moisture content. The dried product was then subjected to infrared spectroscopy to observe the ring-opening process.
[0039] S2, Epoxy Resin E51 Impregnation of Dialdehyde Cellulose: Take 1 g of dialdehyde cellulose A (converted from the moisture content in step S1), add 3 g of epoxy resin E51 and 0.15 mL of coupling agent KH550, mix evenly using a homogenizer, and freeze-dry in a freeze dryer for 24 h to obtain epoxy resin-impregnated dialdehyde cellulose B.
[0040] S3, Preparation of dialdehyde cellulose / epoxy resin composite material: Moistened dialdehyde cellulose B was added to 1.5 g of epoxy resin E51, followed by 4.5 g of hexahydrophthalic anhydride and 0.02 g of 2-4-EMI. After homogenization using a homogenizer, the mixture was placed in an ultrasonic bath at room temperature for 10 min to remove bubbles, yielding a cellulose-modified epoxy resin adhesive, denoted as 0.6DEP (calculated based on the total amount of main substances; the actual amount of dialdehyde cellulose added is approximately 10%).
[0041] Example 2 Compared with Example 1, the only difference is that the mass ratio of sodium periodate to microcrystalline cellulose in step S1 is 0.9 g / g, and the other steps and conditions are the same as in Example 1, resulting in 0.9DEP.
[0042] Example 3 Compared with Example 1, the only difference is that the epoxy resin E51 used in steps S2-S3 is replaced with polyethylene glycol diglycidyl ether, and the other steps and conditions are the same as in Example 1, resulting in 0.6DPEGDE.
[0043] Example 4 Compared with Example 1, the only difference is that the mass ratio of sodium periodate to microcrystalline cellulose in step S1 is 0.9 g / g; the epoxy resin E51 used in steps S2-S3 is replaced with polyethylene glycol diglycidyl ether, and the other steps and conditions are the same as in Example 1, resulting in 0.9DPEGDE.
[0044] Example 5 Compared with Example 1, the only difference is that the mass ratio of sodium periodate to microcrystalline cellulose in step S1 is 0.9 g / g, and the dry weight of dialdehyde cellulose A in step S2 is 0.5 g. The other steps and conditions are the same as in Example 1, resulting in 0.9DEP-5.
[0045] Example 6 Compared with Example 1, the only difference is that the mass ratio of sodium periodate to microcrystalline cellulose in step S1 is 0.9 g / g, and the dry weight of dialdehyde cellulose A in step S2 is 1.5 g. The other steps and conditions are the same as in Example 1, resulting in 0.9DEP-15%.
[0046] Comparative Example 1 Compared with Example 1, the only difference is that the mass ratio of sodium periodate to microcrystalline cellulose in step S1 is 0.3 g / g, and the other steps and conditions are the same as in Example 1, resulting in 0.3DEP.
[0047] Comparative Example 2 Compared with Example 1, the only difference is that step S1 is removed, the amount of dialdehyde cellulose A added in step S2 is 0, and the other steps and conditions are the same as in Example 1, resulting in EP.
[0048] Comparative Example 3 Compared with Example 1, the only difference is that step S1 is removed, and microcrystalline cellulose is used directly to replace dialdehyde cellulose A in step S2. The other steps and conditions are the same as in Example 1, and MEP is obtained.
[0049] Comparative Example 4 Compared with Example 1, the only difference is that the mass ratio of sodium periodate to microcrystalline cellulose in step S1 is 1.2 g / g, and the other steps and conditions are the same as in Example 1, resulting in 1.2 DEP.
[0050] Comparative Example 5 Compared with Example 3, the only difference is that step S1 is removed, the amount of dialdehyde cellulose A added in step S2 is 0, and the other steps and conditions are the same as in Example 3 (i.e. the resin used is polyethylene glycol diglycidyl ether and there is no filler), thus obtaining PEGDE.
[0051] Comparative Example 6 Compared with Example 3, the only difference is that in step S2, microcrystalline cellulose is directly used to replace dialdehyde cellulose A, and the other steps and conditions are the same as in Example 3 (i.e., the resin used is polyethylene glycol diglycidyl ether, and the filler is microcrystalline cellulose), to obtain MPEGDE.
[0052] Comparative Example 7 Compared with Example 3, the only difference is that the mass ratio of sodium periodate to microcrystalline cellulose in step S1 is 0.3 g / g, and the other steps and conditions are the same as in Example 3, resulting in 0.3DPEGDE.
[0053] Comparative Example 8 Compared with Example 3, the only difference is that the mass ratio of sodium periodate to microcrystalline cellulose in step S1 is 1.2 g / g, and the other steps and conditions are the same as in Example 3, resulting in 1.2DPEGDE.
[0054] Performance testing (1) Polarizing microscopy test of resin adhesives: such as Figure 1Figures (a)-(f) show pure epoxy resin E51, MEP, 0.3DEP, 0.6DEP, 0.9DEP, and 1.2DEP resin adhesives, respectively. It can be clearly seen that the size of dialdehyde cellulose gradually decreases with the increase of sodium periodate content. It can also be seen that even with the maximum sodium periodate content, dialdehyde cellulose still has a large number of unreacted crystalline regions, which is conducive to building a stable three-dimensional network structure in the resin system.
[0055] (2) Infrared test of dialdehyde cellulose: Figure 2 Infrared Raman spectroscopy was performed on the dialdehyde cellulose prepared in Examples 1-2, Comparative Examples 1 and 4, and the microcrystalline cellulose used, after freeze-drying. It can be seen that after oxidation with sodium periodate, the cellulose exhibits high spectral density at a wavenumber of 1735 cm⁻¹. -1 A distinct aldehyde stretching vibration peak was observed, and the peak area gradually increased with the increase of sodium periodate dosage. These generated aldehyde groups can react with epoxy groups, ensuring good compatibility with the epoxy resin matrix, uniform dispersion, and preventing agglomeration.
[0056] (3) Figure 3 The viscosity changes (measured using a rotational viscometer after heating in a 25°C water bath for five minutes) of eight samples (Examples 1-2, Examples 5-6, and Comparative Examples 1-4) at different shear rates are demonstrated. When the shear rate is the same, the viscosity of the samples increases rapidly with increasing reaction intensity. Dialdehyde cellulose causes a sharp increase in the viscosity of the epoxy resin adhesive. This is because dialdehyde cellulose, through hydrogen bonds formed by its active aldehyde groups and rigid chain structure, forms a strong, pervasive three-dimensional network structure in the epoxy resin system. This network greatly restricts the free movement of resin molecules and fillers (dialdehyde cellulose), resulting in a sharp increase in macroscopic viscosity. The optimal ratio example 1 (0.6 DEP) in this invention uses moderately oxidized dialdehyde cellulose, resulting in a moderate viscosity and significantly better performance than Comparative Example 1 (0.3 DEP), Comparative Example 2 (EP), and Comparative Example 3 (MEP), facilitating storage and application.
[0057] (4) Figure 4 The changes in the thixotropic index of eight samples (Examples 1-2, Examples 5-6, and Comparative Examples 1-4) are shown. Figure 4It is known that with an addition of only about 10%, the thixotropic index of the resin increases significantly with the degree of oxidation (or the amount of sodium periodate used), increasing by about 6 to 7 times. This is because the aldehyde groups (-CHO) abundant in the DAC molecular chain are extremely strong hydrogen bond acceptors (O atoms), while the remaining hydroxyl groups (-OH) are both donors and acceptors. This makes DAC a powerful "hydrogen bond hub." Uncured epoxy resin molecules have a large number of hydroxyl groups (-OH) and ether bonds (-O-). The aldehyde and hydroxyl groups of DAC can form a dense network of hydrogen bonds with them. These hydrogen bonds form at rest, connecting the resin, curing agent, and DAC itself into a stable three-dimensional network, resulting in high viscosity. When subjected to shear, these secondary bonds are broken, the network disintegrates, and the viscosity decreases. After the shear force is removed, the hydrogen bonds reform, the network recovers, and the viscosity rebounds. This "build-destroy-rebuild" process is highly reversible, perfectly demonstrating thixotropy. The thixotropic index increases significantly with the degree of reaction and amount of dialdehyde cellulose, making it easier to operate during construction.
[0058] (5) Thermal expansion coefficient test: The obtained adhesive sample was placed in a mold for curing. The curing conditions were 80℃ for 1 h and then 100℃ for 3 h. Figure 5 The linear coefficient of thermal expansion (CTE) of six samples (Examples 1-2 and Comparative Examples 1-4) before and after the glass transition temperature is shown. It can be seen that in Comparative Example 3, when the filler is microcrystalline cellulose (MCC), the CTE is actually higher than in Comparative Example 2, regardless of whether it is at high or low temperatures. However, when using dialdehyde cellulose (DAC), the CTE first gradually decreases and then slowly increases. This is because MCC, due to its surface inertness, can only physically fill the resin, resulting in poor interfacial bonding and potential defects, thus failing to reduce or even increasing the coefficient of thermal expansion. In contrast, the active aldehyde groups of DAC can chemically bond with the resin, effectively constraining the thermal motion of the matrix through a strong interface, thereby significantly reducing the coefficient of thermal expansion. However, when its content is too high, excessive local cross-linking can cause internal stress microcracks, leading to a slight increase in the coefficient. 0.9DEP shows the most significant effect, with its CTE decreasing by 65.67% and 49.6% before and after the glass transition temperature, respectively, compared to EP.
[0059] (6) Figure 6The changes in the linear coefficient of thermal expansion (CTE) of the samples prepared in Examples 3-4 and Comparative Examples 5-8 (using polyethylene glycol diglycidyl ether as resin) under the same curing conditions are shown. The general trend is similar to that of epoxy resin E51. After polyethylene glycol diglycidyl ether (PEGDE) is compounded with dialdehyde cellulose (DAC), its CTE initially decreases and then increases with increasing DAC aldehyde content. This is due to the change in the role of DAC. Initially, DAC acts as a crosslinking agent, and its aldehyde groups react with the epoxy groups of PEGDE to form a dense three-dimensional network, restricting the thermal motion of molecular chains and reducing CTE. Later, excessively high aldehyde content leads to self-crosslinking and aggregation of DAC molecules, initiating phase separation and creating defects and micropores at the interface. Unreacted aldehyde groups act as plasticizers, increasing free volume. These factors collectively disrupt the network uniformity and integrity, causing the CTE to increase instead of decrease.
[0060] (7) The cured adhesive layer sample has excellent mechanical properties, with high tensile strength and bonding strength.
[0061] In summary, this invention provides a method for preparing and applying a cellulose-modified epoxy resin adhesive. The reinforcing effect of dialdehyde cellulose significantly improves the thixotropic index and volume expansion rate of the resin. The thixotropic index increases dramatically after adding a small amount of dialdehyde cellulose. Simultaneously, the volume expansion rate is well controlled at different temperatures. For epoxy resin E51, the optimal formulation increases the thixotropic index by approximately 6-7 times. The linear thermal expansion rate of epoxy resin E51 decreases by 65.67% and 49.6% before and after the glass transition temperature, respectively; the expansion rate of polyethylene glycol diglycidyl ether decreases by 44.12%. Compared to common inorganic materials, this invention significantly reduces the required addition amount (around 10%), while having almost no impact on other properties or even enhancing them.
[0062] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a cellulose-modified epoxy resin adhesive, characterized in that, Includes the following steps: S1, microcrystalline cellulose is oxidized with an oxidizing agent to obtain dialdehyde cellulose A; S2, dialdehyde cellulose A is impregnated and dried with a first epoxy resin and a coupling agent to obtain dialdehyde cellulose B; S3, mix dialdehyde cellulose B, second epoxy resin, curing agent and accelerator to obtain cellulose modified epoxy resin adhesive.
2. The method for preparing the cellulose-modified epoxy resin adhesive according to claim 1, characterized in that, In step S1, the oxidant includes sodium periodate; The mass ratio of the oxidant to the microcrystalline cellulose is (0.3-1.2):
1.
3. The method for preparing the cellulose-modified epoxy resin adhesive according to claim 1, characterized in that, In step S1, the oxidation treatment involves adding an oxidant to a microcrystalline cellulose suspension and then reacting it at 30°C to 60°C for 4 to 10 hours.
4. The method for preparing the cellulose-modified epoxy resin adhesive according to claim 1, characterized in that, The dry weight of the dialdehyde cellulose A accounts for 5% to 15% of the mass of the cellulose-modified epoxy resin adhesive.
5. The method for preparing the cellulose-modified epoxy resin adhesive according to claim 1, characterized in that, In step S2, the ratio between the first epoxy resin and the coupling agent is (2-4) g: (0.1-0.2) mL; The coupling agent includes a silane coupling agent.
6. The method for preparing the cellulose-modified epoxy resin adhesive according to claim 1, characterized in that, Both the first epoxy resin and the second epoxy resin include epoxy resin E51 or polyethylene glycol diglycidyl ether. The mass ratio of the first epoxy resin to the second epoxy resin is (1.5~2.5):
1.
7. The method for preparing the cellulose-modified epoxy resin adhesive according to claim 1, characterized in that, In step S3, the curing agent is methylhexahydrophthalic anhydride or methyltetrahydrophthalic anhydride; The amount of curing agent used is 80% to 120% of the total mass of the first epoxy resin and the second epoxy resin.
8. The method for preparing the cellulose-modified epoxy resin adhesive according to claim 1, characterized in that, In step S3, the accelerator includes one or more of triethanolamine, 2-methylimidazole, and 2-ethyl-4-methylimidazole; The amount of the accelerator is 0.2% to 0.8% of the total mass of the first epoxy resin and the second epoxy resin.
9. The cellulose-modified epoxy resin adhesive prepared by the preparation method according to any one of claims 1-8.
10. A cellulose-modified epoxy resin coating, characterized in that, It is formed by curing the above-mentioned adhesive.